Measuring tourism emissions at destination level: Australia case - Tien Pham; Xianming Meng; Susanne Becken (Annals of Tourism Research Empirical Insights, 2022)
Decarbonising tourism is an immeasurable challenge but increasingly recognised as inevitable. This has prompted vast developments in theoretical models by academics and indicators by peak bodies to explore the pathways. One limitation to the pathways is the lack of emission data. This research presents a framework integrating the principles of TSA with the National Greenhouse Accounts. Tourism emissions are estimated and examined by destinations, producing industries and visitor types. The framework is applied to destinations in the State of Queensland, Australia, to illustrate the types of results and insights that can be produced for decision-makers. Mitigation policies can then be tailored to the specific context of each destination, increasing effectiveness and ability to balance economic benefits with reducing emissions.
Keywords: 330; Carbon footprint; Tourism emissions; Tourism satellite account; Destinations; Carbon account framework